2021
DOI: 10.3390/met11081267
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Biocompatibility Evaluation of a New Co-Cr-B Alloy with Potential Biomedical Application

Abstract: Cobalt–chromium (Co-Cr) alloys have been used in a wide variety of biomedical applications, including dental, cardiovascular, and orthopedic devices. In vitro studies have shown that the mineralization of cells involved in osteogenesis is regulated by boron. The development of a new cobalt-chromium-boron (Co-Cr-B) alloy improves the mechanical properties of the metal, such as wear resistance, and meets biocompatibility requirements. Therefore, the objective of this study was to evaluate the osteogenic differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Co-based alloys show better corrosion, wear, and mechanical properties and are used in bioimplant applications. The in vivo and in vitro studies confirmed that Co-based alloys show better biocompatibility and can be used for the manufacturing of surgical implants such as in the hip, knee, shoulder, and fractured bone surfaces [76,77]. The most widely used combination of Co alloys are Co-Cr-Mo owing to their unique combination of strength and ductility.…”
Section: Co-cr Alloysmentioning
confidence: 71%
“…Co-based alloys show better corrosion, wear, and mechanical properties and are used in bioimplant applications. The in vivo and in vitro studies confirmed that Co-based alloys show better biocompatibility and can be used for the manufacturing of surgical implants such as in the hip, knee, shoulder, and fractured bone surfaces [76,77]. The most widely used combination of Co alloys are Co-Cr-Mo owing to their unique combination of strength and ductility.…”
Section: Co-cr Alloysmentioning
confidence: 71%
“…Cobalt and cobalt alloys possess excellent antimicrobial properties, with widespread use in a variety of biomedical applications such as dentistry, cardiovascular treatments, and orthopedic devices [ 50 ]. Co alloys exhibit favorable corrosion resistance without pitting and crevice corrosion, as these alloys can release Co ions in solutions to stabilize the passive film and Co ions can be repetitively released in the wear situation [ 51 ].…”
Section: Metal Biomaterials With the Potential Application As Cardiov...mentioning
confidence: 99%
“… Metal biomaterials Advantages Disadvantages References 316L SS Low cost Good mechanical properties, biocompatibility, corrosion resistance and machinability Contain high levels of Cr and Ni which has sensitization and carcinogenicity, causing immunoreactions and inflammatory responses [ 28 ] Ti and Ti alloys Good biocompatibility, corrosion resistance, mechanical integrity and stability Relatively biologically inert surface No antimicrobial properties Poisoning of the body caused by the release of metal ions and their accumulation in the soft tissues of the body. [ 62 , 63 ] Mg and Mg alloys Biodegradable Good mechanical strength and biocompatibility Non-toxic Low thrombogenicity Rapid degradation Poor ductility [ 64 ] Zn and Zn alloys Biodegradable Moderate corrosion rate Adjustable mechanical properties Good biocompatibility Non-toxic Low mechanical strength [ 65 , 66 ] Co and Co alloys Excellent antimicrobial properties Good mechanical strength and corrosion resistance Co is toxic to fibroblasts and can trigger inflammatory mediator [ 50 , 51 , 67 ] High entropy alloys Well-balanced mechanical properties Good biocompatibility High degree of design freedom Immature preparation process High cost [ 56 , 57 ] …”
Section: Metal Biomaterials With the Potential Application As Cardiov...mentioning
confidence: 99%
“…Compared with stainless steel, Co-based alloys are characterized by superior strength. Despite their difficult fabrication, Co-based alloys are more resilient to corrosion and wear and display better biocompatibility [65]. Alloyed with Cr and Mo, some Co-based alloys like Co-Cr-Mo and Co-Ni-Cr-Mo are specially used for implants in the hip, knee and shoulder prosthesis [66].…”
Section: Co-cr Alloysmentioning
confidence: 99%
“…Additionally, their alloying elements such as Ni, Cr and Mo were proven to be toxic when released from the implant surface in the body fluid during corrosion processes. Excessive accumulation of these elements in organs such as kidneys, liver, lungs and blood cells can trigger their damage [65].…”
Section: Co-cr Alloysmentioning
confidence: 99%